The economic prospects of the CIS sources of long term growth - Ofer, Gur.; Pomfret, Richard W. T.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar Pub., 2004)
This book brings together ten original studies on the transition and growth experience and the foundations for long-term growth of the newly independent states created by the dissolution of the Soviet Union.
1. Introduction -- 2. Down and up the stairs : paradoxes of Russian economic growth -- 3. Transition and growth in Belarus -- 4. Ukraine : the lost decade ... and the coming boom? -- 5. Barriers to growth in Moldova -- 6. Explaining growth in Armenia : the pivotal role of human capital -- 7. Turkmenistan : economic autocracy and recent growth performance -- 8. The Uzbek paradox : progress without neo-liberal reform -- 9. Tajikistan's growth performance : the first decade of transition -- 10. Economic growth in Kyrgyzstan -- 11. Natural resources and economic growth in Kazakhstan -- 12. Conclusions.
Includes bibliographical references and index.
Keywords: Former Soviet republics -- Economic conditions -- Congresses; Electronic books